Expression of MAO gene in both starved and non-starved glioblastoma cancer cell line: Expression of MAO gene in glioblastoma - abdulghany, zaynab; Noah A. Mahmood (Iraqi Journal of Cancer and Medical Genetics, 2023)
Background: The relationship between cancer cell aggression induced by serum starvation and cell metastasis has been studied. Serum starvation is a typical way to induce tumor cell apoptosis, and stress may affect cell growth. Monoamine oxidase A (MAOA) was discovered as a mitochondrial enzyme that plays a role both as tumor suppressor and as an oncogenic factor in promoting tumor cell growth. Glioblastoma is a deadly cancer in the 4th rank reported in the Iraqi Cancer Registry 2020. Aim of the study: The deprivation of serum from cultured media for glioblastoma cancer cell line (AMGM5) was tested after three different durations 24, 48, and 72h.Methods: Comparison of MAO gene expression between starved and non-starved glioblastoma cell lines was measured using real-time PCR. Results: The results indicated an increase in MAO gene expression in serum deprivation of cultured cells compared significantly (p